Drug‐induced liver injury is frequently associated with severe cutaneous adverse drug reactions: experience from two Australian tertiary hospitals. Issue 5 (2nd May 2018) - Fang, Wendy C.; Adler, Nikki R.; Graudins, Linda V.; Goldblatt, Caitlin; Goh, Michelle S. Y.; Roberts, Stuart K.; Trubiano, Jason A.; Aung, Ar Kar
Abstract: Background: Drug‐induced liver injury (DILI) can be associated with certain cutaneous adverse drug reaction (cADR). Aims: To demonstrate the prevalence of DILI in patients with cADRs. Severity and patterns of liver injury, risk factors, causal medications and outcomes are also examined. Methods: A retrospective cohort study of patients with cADRs was conducted across two hospitals in Australia. Patients were identified through cross‐linkage of multiple databases. Results: One hundred and four patients with cADRs were identified. Of these, 33 (31.7%) had liver injury, representing 50% of patients with drug reaction with eosinophilia and systemic symptoms, and 30.2% of patients with Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN). Most cases of liver injury (69.7%) were of a cholestatic/mixed pattern with severe disease in 18.2%. No significant risk factors for development of liver injury were noted, but peripheral lymphocytosis may represent a risk in patients with SJS (odds ratio, OR = 6.0, 95% confidence interval, CI: 1.8–19.7, P = 0.003). Antimicrobials were the most common class to be implicated in DILI. The median length of inpatient stay was longer in patients with liver injury compared to those without (19 vs 11 days, P = 0.002). The mortality rate in those with liver injury was 15.2% and 9.9% in those without. No patients required liver transplantation. Conclusions: DILI commonly occurs in patients with cADRs and is associated with longer inpatient stay. Patients with SJS/TEN and peripheral lymphocytosis appear to be at higher risk for developing associated liver injury.